Risposte adattative in molluschi bivalvi in uno scenario di cambiamenti climatici - Casadoro, Giorgio; Marin, Maria Gabriella (Università degli studi di Padova, 2012)
The increment of atmospheric CO2 produced by human activities is responsible for both global warming and progressive acidification of oceans. In particular, ocean acidification has negative consequences for all those organisms that build calcareous structures, modifying their physiological activities, survival, and growth, and causing reduction in calcification rate. In this context, the bivalves Mytilus galloprovincialis, Chamelea gallina, Callista chione, Mimachlamys varia were chosen to investigate the effects of decreased pH, increased temperature and variations in salinity, as predicted in climate change scenarios, on physiological, immunological, biochemical responses, growth and shell damage. The choice of these species took into account their different habitats, which may make them differently susceptible to climate change effects: two inshore (M. galloprovincialis, C. gallina) and two offshore (C. chione, M. varia) species were studied. Short-term experiments on adults were performed for all species and long-term experiments were performed on juveniles of M. galloprovincialis and C. gallina. An experimental plant was set up in the laboratory to test simultaneously the effects of temperature and pH on adult bivalves. Six combinations were tested, three values of pH (8.1, 7.7, 7.4) and two temperatures (22, 28°C: M. galloprovincialis, C. gallina; 16, 22°C: C. chione; 18, 26°C: M. varia). In M. galloprovincialis and C. gallina the same combinations of temperature and pH were tested at three salinities (28, 34, 40 psu). To test the effect of reduced pH (7.4) on juvenile mussels and clams, an outdoor experimental plant was set up, supplied with sea water flowing in continuous from the sea. Two experiments were carried out, the former, on both M. galloprovincialis and C. gallina, lasted six months, the latter, on M. galloprovincialis only, was three-month long. The aim of this outdoor experiment was to operate in experimental conditions as similar as possible to mesocosms, except for pH value in treated ...